Retention and attrition of experienced Malay male architects in Malaysian architectural design consultant firms in the Klang Valley, Malaysia - Mohd Hisham Ariffin; Ismah Sumayyah Mohd Amar (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Malaysian construction industry suffers from a high rate of attrition within its professional consultant firms. Employees’ job satisfaction is related to higher productivity and their continued employment in their current firms. Employment attrition hinders the firms from enhancing their competitiveness through organizational commitment and increased productivity. The Malays currently constitute the majority of the workforce in construction related professions including architecture. However, the attrition of female professional employees from the architecture consulting field drastically increases after the ages of 34 years. This implies that it is appropriate for architecture firms to focus on ways to retain and prevent the attrition of their experienced male Malay architects to other firms and thus enhance the firms’ competitiveness. Past relevant researches mostly focused on female architects and on the work environment challenges that did not directly address the attrition and retention motivations. This exploratory qualitative interview research was done into the employment retention and attrition reasons of a purposive sample of ten experienced male professional Malay Architects in Malaysian architecture consulting firms in the Klang Valley. These reasons were uncovered through analysis of interview transcripts with the sample cohorts. Qualitative data coding generated employment retention and attrition meaning units based on the need categories in Alderfer’s ERG motivation theory. The generated categories were existence needs (physiological, material security, convenience) relatedness needs (group belongingness, social needs, family obligations, friendship obligations, social obligations and social esteem), growth (selfesteem and self-actualization) and intrinsic motives (choice, progress, competence and meaningfulness). All respondents remained in the firm when the employment provided convenience and self-esteem to them and from a sense of group obligations for the firm. Yet they would seek employment elsewhere when the gratuities with the current employer cannot fulfill their physiological needs. They also leave when the employment does not fulfil self-esteem needs. Thus, a theme evident within the responses is that high order (growth) needs and mid-order (relatedness) needs retain male professional Malay Architects while the failure to meet low order (existence) needs and high order (growth) needs motivate their employment attrition. Further investigations are warranted due to the limitations of the sampling methodology. The findings nonetheless provide guidance for future research that can provide generalized findings.